2022
DOI: 10.3390/plants11020146
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Multiple Organellar RNA Editing Factor (MORF) Family in Kiwifruit (Actinidia chinensis) Reveals Its Roles in Chloroplast RNA Editing and Pathogens Stress

Abstract: Kiwifruit (Actinidia chinensis) is well known for its high vitamin C content and good taste. Various diseases, especially bacterial canker, are a serious threat to the yield of kiwifruit. Multiple organellar RNA editing factor (MORF) genes are pivotal factors in the RNA editosome that mediates Cytosine-to-Uracil RNA editing, and they are also indispensable for the regulation of chloroplast development, plant growth, and response to stresses. Although the kiwifruit genome has been released, little is known abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…Latest research reported that MORF involved in plant growth, development, stress response such as survival of seedling rice, drought resistance in poplar, and pathogen resistance in tobacco ( Wang et al, 2019 ; Zhang et al, 2019 ; Yang et al, 2020 ). Our results showed the downregulation of MORF genes under alkaline stress and agreement with the findings of Zhang et al (2019) and Xiong et al (2022) . Similarly, NbMORF8 which is present in the mitochondria and negatively enhance the immunity to Phytophthora pathogens in tobacco ( Yang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Latest research reported that MORF involved in plant growth, development, stress response such as survival of seedling rice, drought resistance in poplar, and pathogen resistance in tobacco ( Wang et al, 2019 ; Zhang et al, 2019 ; Yang et al, 2020 ). Our results showed the downregulation of MORF genes under alkaline stress and agreement with the findings of Zhang et al (2019) and Xiong et al (2022) . Similarly, NbMORF8 which is present in the mitochondria and negatively enhance the immunity to Phytophthora pathogens in tobacco ( Yang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…More and more members of PPR proteins are reported but the exact number of involved PPR is still missing ( Schmitz-Linneweber and Small, 2008 ). Similarly, in kiwifruit, MORF2 and MORF9 are well documented; they interact with NADH4 and are very important for RNA editing of chloroplast genome ( Xiong et al, 2022 ) while MORF8 interact with MORF1 and MORF2 ( Zehrmann et al, 2015 ; Huang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many mutants with impaired editing of specific sites exhibited strong deleterious phenotypes, even lethality [ 9 12 ]. In our previous studies, we found that the RNA editing events in grapes were reduced in response to heat stress [ 11 ], the RNA editing events in kiwifruits were reduced in response to pathogens infection [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…When plants are subjected to the stress of abiotic and biotic environments, they can usually adapt to changing and complex environments by inducing the expression of stress genes [ 1 , 2 , 3 ]. Many members of the plants’ gene families were involved in plant-specific development and a series of stresses [ 4 , 5 ]. For example, multiple organellar RNA editing factor ( MORF) genes regulate the plant–pathogen interaction by controlling the extent of RNA editing; growth regulatory factors ( GRF) genes show different expression patterns in different tissues or under drought and salt stress; MaGRAS plays an important role in response to abscisic acid (ABA) and abiotic stress [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many members of the plants’ gene families were involved in plant-specific development and a series of stresses [ 4 , 5 ]. For example, multiple organellar RNA editing factor ( MORF) genes regulate the plant–pathogen interaction by controlling the extent of RNA editing; growth regulatory factors ( GRF) genes show different expression patterns in different tissues or under drought and salt stress; MaGRAS plays an important role in response to abscisic acid (ABA) and abiotic stress [ 5 , 6 , 7 ]. The SIMILAR-TO-RCD-ONE ( SRO ) plays a vital role in plants coping with abiotic and biotic stresses and participating in growth and development [ 4 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%